Numerical Simulation Study on the Seismic Performance of Prefabricated Fiber-Reinforced Concrete Beam–Column Joints With Grouted Sleeve Connections - Mei-Ling Zhuang; Jinsheng Cheng; Dongsong Fei; Chuanzhi Sun; Zhenbo Wang; Baodong Chen; Yan Qiao (International Journal of Concrete Structures and Materials, 2024)
Abstract Based on the available experimental data, fiber models for four prefabricated fiber-reinforced concrete beam–column joint specimens with grouted sleeve connections are first developed in OpenSees software. Then, the simulated seismic performance of the specimens is compared with the experimental results. Finally, the effects of axial load ratio and shear-to-span ratio on the seismic performance of the specimens are further investigated numerically. The results indicate that Concrete02 material model and Reinforcing Steel material model can accurately simulate the constitutive relationship of concrete and reinforcing steel, respectively; the beam–column joint elements can accurately simulate different damage behaviors of the joint zone. Fiber-reinforced concrete can significantly improve the seismic performance of the specimens. The relative errors of the simulated seismic performance indexes are about 15%. It is recommended that the optimum value of shear-to-span ratio for prefabricated FRC BCJs is 2.0–2.5. The effect of axial load ratio on the seismic behavior of PBCJs-CM is very small, and can be negligible in the case that the prefabricated FRC BCJs has a moderate value of shear-to-span ratio. The fiber model developed in this article can provide a numerical simulation basis for subsequent studies of prefabricated fiber-reinforced concrete beam–column joint specimens with grouted sleeve connections.